2022
DOI: 10.1002/advs.202103689
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of Malignant Glioma by Noninvasive Administration of TLR9 Agonist CpG Nano‐Immunoadjuvant

Abstract: Immunotherapy with toll like receptor 9 (TLR9) agonist CpG ODN offers an emergent strategy to treat life-threatening malignant glioma. CpG is typically applied invasively by intracranial and intrathecal administration which induces not only poor compliance and lessened potency but also possibly strong adverse effects and immunotoxicity. Here, it is reported that immunotherapy of murine LCPN glioma is greatly boosted by polymersome-steered intravenous and intranasal brain delivery of CpG. CpG is efficiently loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…[ 113 ] Unmethylated cytosine‐phosphate‐guanine (CpG), an immunostimulatory nucleic acid, is a powerful toll‐like receptor‐9 (TLR9) agonist to induce a cascade of adaptive and innate immune responses, and it has been widely used as an adjuvant. [ 114 ] CpG can specifically bind to TLR9 to induce the production of cytokines such as IFN‐ γ , IL‐12, IL‐6, TNF‐ α , and increase the level of co‐stimulatory molecules expressed by B cells and DCs. [ 115 ] In particular, clinical trial results have indicated that CpG can enhance T cells responses to boost the antitumor effect when it is used as a single agent or it is combined with antineoplastic therapies.…”
Section: Icd Induced By Nddss In Combination With Immunotherapymentioning
confidence: 99%
“…[ 113 ] Unmethylated cytosine‐phosphate‐guanine (CpG), an immunostimulatory nucleic acid, is a powerful toll‐like receptor‐9 (TLR9) agonist to induce a cascade of adaptive and innate immune responses, and it has been widely used as an adjuvant. [ 114 ] CpG can specifically bind to TLR9 to induce the production of cytokines such as IFN‐ γ , IL‐12, IL‐6, TNF‐ α , and increase the level of co‐stimulatory molecules expressed by B cells and DCs. [ 115 ] In particular, clinical trial results have indicated that CpG can enhance T cells responses to boost the antitumor effect when it is used as a single agent or it is combined with antineoplastic therapies.…”
Section: Icd Induced By Nddss In Combination With Immunotherapymentioning
confidence: 99%
“…Recently, various immunoadjuvant-loaded NPs have been developed to enhance the abscopal effect of RT. 42,432,[514][515][516][517] For example, Patel et al designed bacterial membranecoated NPs (BNPs) to promote RT to elicit systemic antitumor immunity against local tumors and metastatic relapse. 518 The BNPs were composed of four components.…”
Section: Strategies For Synergistic Induction Of Abscopal Effect By R...mentioning
confidence: 99%
“…This was a redox responsive formulation, which led to the stimulation of pro-inflammatory cytokine production and DC maturation in vivo, as well as the reprogramming of the tumor immune microenvironment by inducing more immunogenic cell death (ICD) (of tumor cells), CD8 + T cells, and activated antigen presentation cells (APCs). Combined use of this “smart” brain-permeable nano-immunoadjuvant with radiotherapy further boosted the anti-cancer effect and improved the survival rate in mice ( Figure 7 ) [ 192 ].…”
Section: Gbm–immunotherapy–bioengineeringmentioning
confidence: 99%
“…Abbreviations: ApoE: Apolipoprotein E, IFN-γ: Interferon gamma, TNF-α: Tumor necrosis factor alpha, IL-6: Interleukin 6, CNS: Central nervous system, CLN: Cervical lymph node, PBS: Phosphate buffer saline. Reprinted with permission from [ 192 ].…”
Section: Figurementioning
confidence: 99%